2021
DOI: 10.1038/s41598-021-94368-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale structures as spots of increased fish concentration in the open ocean

Abstract: Oceanic frontal zones have been shown to deeply influence the distribution of primary producers and, at the other extreme of the trophic web, top predators. However, the relationship between these structures and intermediate trophic levels is much more obscure. In this paper we address this knowledge gap by comparing acoustic measurements of mesopelagic fish concentrations to satellite-derived fine-scale Lagrangian Coherent Structures in the Indian sector of the Southern Ocean. First, we demonstrate that highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…This was considered as a stadium shape with the two semi-circles centered on the starting and ending points of the transect, respectively. The radius of the stadium semi-circles was considered 0.1°, which is in accordance with previous studies 49, 53, 54 . The stadium was filled with virtual particles separated by 0.01°.…”
Section: Environmental Context For Data Analysissupporting
confidence: 71%
“…This was considered as a stadium shape with the two semi-circles centered on the starting and ending points of the transect, respectively. The radius of the stadium semi-circles was considered 0.1°, which is in accordance with previous studies 49, 53, 54 . The stadium was filled with virtual particles separated by 0.01°.…”
Section: Environmental Context For Data Analysissupporting
confidence: 71%
“…In mesotrophic areas, the daily detection of productive oceanic features (chlorophyll-a fronts) from ocean color satellite sensors (currently MODIS-Aqua) is a good generic proxy for food availability to fish populations (Druon et al, 2021). When productivity fronts are active long enough (from weeks to months) to allow the development of mesozooplankton populations (Druon et al, 2019), they were shown to attract epiand mesopelagic fish and top predators (Olson et al, 1994;Polovina et al, 2001;Briscoe et al, 2017;Druon et al, 2017;Baudena et al, 2021). After an initial development phase of 3-4 weeks, the mesozooplankton biomass reached substantial levels in the persistent and not necessarily stationary chlorophyll-a fronts, i.e.…”
Section: The Biotic Environmental Variablesmentioning
confidence: 99%
“…Small and large chlorophyll-a fronts were derived from and refer to different levels of chlorophyll-a gradient values (see the SM for details on the chlorophyll-a gradient calculation). Based on the link described above between productivity fronts and biomass of low and high trophic levels (e.g., Olson et al, 1994;Polovina et al, 2001;Druon et al, 2019;Druon et al, 2021;Baudena et al, 2021), high chlorophyll-a gradient levels are assumed to correspond, when persistent, to productivity fronts with an important capacity to sustain well-developed food chains and foraging opportunities for predators. The five-day chlorophyll-a gradient values were extracted in a 25 km radius centered on the (day and location of) blue shark presence data for each size and sex class, and a minimum of 33% coverage was set to accept the mean gradient value (5-day and 25 km-radius mean value).…”
Section: The Biotic Environmental Variablesmentioning
confidence: 99%
“…Mixing across frontal structures, including diffusivity even in its smallscale, might have an important impact on the dispersion of passive tracers in the ocean. Unlike horizontal stirring that reinforces the tracer gradients across fronts, small-scale diffusivity processes tend to reduce and smooth the gradients [14,65,66]. Nevertheless, in this study, we particularly highlighted the impact of the horizontal stirring in controlling the formation and the evolution of the transport patterns, shaping, in turn, the trajectory of the oil tracer.…”
Section: Discussionmentioning
confidence: 71%